Wave Climate Effects Upon Changing Barrier Island Morphology, Kouchibouguac Bay, New Brunswick - Bryant, Edward (Atlantic Geoscience, 1978)
A quandary as to the role of storms in initiating barrier island morphological change in the Gulf of St. Lawrence has been posed by recent research. Although major changes are evident from historical documentation, none of the processes responsible hos been witnessed since 1970. Detailed calculations of the nearshore wave power climate have been used in conjunction with historical evidence and short term profile measurements between 1970-1978 to resolve this problem in Kouchibouguac Bay, New Brunswick. Although the individual effects of seasonal storms are random along these barrier islands, the additive effects do reflect the overall nearshore wave climate. Greatest change has been wrought in those areas having highest wave power components normal and parallel to shore. If barrier segments susceptible to modification can be predicted for Kouchibouguac Bay, definition of nearshore wave climates could be used to determine such changes elsewhere in the Gulf.